Enhancing Forecast Verification in National Meteorological and Hydrological Services - Thomas C. Pagano; Elizabeth E. Ebert; Mohammadreza Khanarmuei (Meteorological Applications, 2025)
ABSTRACT Forecast verification is an essential function of National Meteorological and Hydrological Services (NMHSs), underpinning their ability to deliver accurate, reliable, and actionable weather, climate, and water‐related information. As NMHSs face increasing demands for transparency, accountability, and continuous improvement, they require robust systems to assess and enhance the quality of their forecasts. This article presents a holistic forecast verification capability development framework, built from over a decade of focused effort at the Australian Bureau of Meteorology. The framework integrates best practices in governance, data management, verification metrics, and communication. It acknowledges the importance of user‐centered approaches and highlights areas where verification practices can align with user needs. To support NMHSs in adopting this framework, the article introduces two practical tools: a Verification Planning Template for establishing new verification activities and systems and a Gap Analysis and Maturity Assessment (GAMA) tool for benchmarking and advancing existing practices. These tools provide structured guidance for planning, evaluating, and improving verification within a NMHS, with the ultimate goal of delivering higher quality forecasts that meet diverse stakeholder needs. The Bureau's progress in implementing this framework demonstrates significant benefits, including improved forecast quality, enhanced coordination across verification efforts, and greater trust among users. However, challenges such as data availability, system integration, and resourcing remain pervasive, both within the Bureau and globally. The tools and insights shared in this article offer a pathway for NMHSs to overcome these obstacles, enabling them to better respond to evolving user expectations and operational demands. This work highlights the value of fostering a strong verification culture, supported by collaboration and knowledge sharing across the international meteorological community. By applying the principles and tools presented here, and customizing them to their circumstances, NMHSs can advance toward resilient, evidence‐based verification practices and capabilities that enhance forecast reliability and stakeholder confidence worldwide.